2004
DOI: 10.1249/01.mss.0000126805.32659.43
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the SenseWear Pro Armband??? to Assess Energy Expenditure during Exercise

Abstract: It appears that it is necessary to apply exercise-specific algorithms to the SenseWear Pro Armband to enhance the accuracy of estimating energy expenditure during periods of exercise. When exercise-specific algorithms are used, the SenseWear Pro Armband provides an accurate estimate of energy expenditure when compared to indirect calorimetry during exercise periods examined in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
272
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 293 publications
(289 citation statements)
references
References 10 publications
10
272
1
Order By: Relevance
“…However, no prior publication has suggested that the data collected by the physiologic sensors significantly may reduce the error in EE compared to accelerometry alone, in either normal or diseased subjects. This improvement in measurement accuracy likely due to the additional sensors may account for previous reports of improved accuracy of the PAM over a broader range of exercise intensities (42) and during activities such as upper arm exercise and cycling (21,41), which are reported to be less accurately measured using accelerometers alone (36).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, no prior publication has suggested that the data collected by the physiologic sensors significantly may reduce the error in EE compared to accelerometry alone, in either normal or diseased subjects. This improvement in measurement accuracy likely due to the additional sensors may account for previous reports of improved accuracy of the PAM over a broader range of exercise intensities (42) and during activities such as upper arm exercise and cycling (21,41), which are reported to be less accurately measured using accelerometers alone (36).…”
Section: Discussionmentioning
confidence: 87%
“…The PAM in this study has previously been validated in normal subjects (21,41,42) and we have additionally documented its reproducibility and accuracy in COPD subjects. However, we further demonstrated that either the PAM proprietary software modeling or (most likely) the additional sensors improved significantly the explained variance in EE determination compared to the accelerometer data alone, from 68% to 88%.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…39 Interestingly, physical activity was not increased by CPAP treatment, suggesting that OSA per se is not the main contributor to reduced physical activity levels. 40 In our study, we measured physical activity patterns with an accelerometer validated in healthy subjects 41 and in diabetics. 34 This device, which has also been recently validated in OSA during sleep, 39 is considered one of the most reliable means of estimating physical activity and its patterns in free living conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The activities in this category (dressing, washing and drying dishes, and folding laundry) are activities that use a large degree of upper extremity movement. Jakicic et al (34) found overestimation by the SWA of 21.7% in an arm ergometry task, despite finding underestimation in the other activities included in the exercise protocol. This might signify that the SWA does not accurately represent energy expenditure accrued during upper extremity activities.…”
mentioning
confidence: 94%